An Oral Rinse Active Matrix Metalloproteinase-8 Point-of-Care Immunotest May Be Less Accurate in Patients with Crohn’s Disease - Jaana Rautava; Ulvi K. Gürsoy; Adrian Kullström; Eija Könönen; Timo Sorsa; Taina Tervahartiala; Mervi Gürsoy (Switzerland, 2022)
The diagnostic accuracy of point-of-care (PoC) applications may be compromised in individuals with additional inflammatory conditions. This cross-sectional study examined the performance of a commercial oral rinse active matrix metalloproteinase-8 (aMMP-8) PoC immunotest in individuals with (n = 47) and without Crohn’s disease (CD) (n = 41). Oral rinse collected from the participants was analyzed by the PoC immunotest. Molecular forms and fragments of salivary MMP-8 were detected by western immunoblotting. The sensitivity of the immunotest for periodontitis was 60.0% in the CD group and 90.0% in the control group. The respective specificity was 75.0% and 80.0%. In both groups, clinical diagnosis of periodontitis exhibited a significant association with the immunotest results, however, the odds ratio (OR) was more than ten-fold in controls (OR 54.3, 95% CI: 3.1–953, p = 0.006) in comparison to CD patients (OR 5.2, 95% CI: 1.3–21.6, p = 0.022). According to Western immunoblot results, the immunotest MMP-8 positivity was not related to elevated levels of molecular forms and fragments of MMP-8 in the CD group, as in the control group. The diagnostic accuracy of the aMMP-8 PoC oral rinse immunotest is reduced in CD patients, which may be related to lower levels or undetectable complexes.